POLA KADERISASI POLITIK MELALUI SAYAP PARTAI PEREMPUAN (Studi Kasus Perbandingan Partai Golongan Karya (Golkar) dan Partai Nasional Demokrat (NasDem) Kota Semarang) - Wahyu herryansyah putra; Fitriyah - - (Journal of Politic and Government Studies, 2020)
Political parties have a very important role and role in a democratic system, so that the recruitment and caderization of political parties has become a strategic function in increasing the name of political parties and increasing the number of members. Political caderization is carried out by political parties to members and not members (Harris, 2016). The internal caderizationfor the political party member is carried out by party itself, while for the expansion of the mass base external to the party can be done by the party wings (political party underbows). The role of the party wings is as a bridge for Political Parties to reach all groups of society, including youth, women and others occupation group, who are the party masses sources. Researchers are interested to study the role of women party wings in the Golongan Karya Party (Golkar) and the National Democratic Party (NasDem) to political caderuzation. The namely the wings party are Golkar Party Women's Union (KPPG) and the Malahayati Women's Guard (Garda Wanita Malahayati) from the NasDem Party. Research based on think every political party has a caderization pattern or system in accordance with the thought system and strategy developed by each political party. This study aims to explain the process of caderization female party members carried out by the Golkar Party and NasDem Party in Semarang City through the women party wings and the barriers they face. This study uses primary and secondary data sources. Data methods used are interviews and documentation. The data analysis method used was qualitative data analysis. The results showed that the cadre process was not patterned, then similarities were found in the both parties cadre process, where the authority of the political caderization function by womens party wings was more focused on efforts to expand members. The other hand, the main political caderization function by the Golkar Party and the NasDem Party itself. Women party wings held caderization role which are unstructured. The obstacles to thewomen party wings in carrying out its caderization function stems from its limited authority. The political caderizationby the Golkar Party and the NasDem Party of Semarang City, including by the womenparty wings was not running optimally, so it failed to gain significant seats and failed to deliver women's electability in the 2019 Semarang City Election. This study recommends further research in other areas.